(3GdYdd hGdCYQGV dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3Ef Ghd eG jfHZj dfG Gf fPcQg, eG GdTF GdPj fSejg eQVkG jYde eG ZQV gPg GdebGdI , hEdi Ci TF jbUO HgG , hGdKGfj HYO gPG(B: (3ce jHdZ GdCeQGV GdHSjWI s
(3BNQgG (B:s
(3hYdi gPG GdeKGd jecfc Cf JSJNQL aj LejY CLfGS GdCYQGV CjgG jJHY HYVgG HYVkG OGFekG, hCjgG dGjJHY OGFekG QCjJ Cf CbWY GdcdGe gfG JeJ GdebGdI GdSGOSI s
(3GfXQ eY GdCYVGA GdBdeI dLGdjfhS HQbe (B326 (3ef gPG GdagQSs
(3fSNI KGdKIs
(3hGhQbI GdChdi HNW MOjKs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs